Pengaruh CSR, Kinerja Keuangan dan GCG Terhadap Nilai Perusahaan - Prihantoro, Sony Anggun; Pramono, Hadi; Fitriati, Azmi; Wibowo, Hardiyanto (Akuisisi : Jurnal Akuntansi, 2025)
The aim of this research is to empirically test the influence of corporate social responsibility (CSR), financial performance and GCG on company value. This research uses the variables Tobins'q, ROA, GCG and liquidity control variables. The method used is the multiple linear regression method. The sample used is a general banking company registered on the IDX that publishes an annual report and a sustainability report for the period 2018-2022. The research results show that the audit committee and liquidity have a positive effect on company value. CSR, the proportion of independent commissioners and the educational background of directors have no effect on company value. ROA and institutional ownership have a negative effect on company value